2017
DOI: 10.1177/0840470417696708
|View full text |Cite
|
Sign up to set email alerts
|

Physician leadership development: Evidence-informed design tempered with real-life experience

Abstract: This article describes key considerations for creation of evidence-informed in-house physician leadership development. Ten elements extracted from a scan of the peer-reviewed and grey literature are presented, and key learnings at the Queen Elizabeth II Health Sciences Centre, a quaternary academic health sciences centre in Halifax, Nova Scotia, are highlighted. Each element is briefly described with practical considerations and challenges to implementation outlined in the context of the former Capital Distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Previous studies of physician leadership have highlighted the need to increase leadership training for physicians ( Canadian Medical Association [CMA], 2012 ; Gallagher et al , 2017 ; Snell et al , 2016 ) given the limited coverage of leadership in existing undergraduate medical curricula. While courses and continuing professional development certifications exist for general leadership needs ( Canadian Medical Association Joule, 2021 ; Canadian Society of Physician Leaders, 2021 ; Jolemore and Soroka, 2017 ), training targeting the specific skills needed for pandemic leadership should be incorporated into pandemic planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of physician leadership have highlighted the need to increase leadership training for physicians ( Canadian Medical Association [CMA], 2012 ; Gallagher et al , 2017 ; Snell et al , 2016 ) given the limited coverage of leadership in existing undergraduate medical curricula. While courses and continuing professional development certifications exist for general leadership needs ( Canadian Medical Association Joule, 2021 ; Canadian Society of Physician Leaders, 2021 ; Jolemore and Soroka, 2017 ), training targeting the specific skills needed for pandemic leadership should be incorporated into pandemic planning.…”
Section: Discussionmentioning
confidence: 99%
“…While studies have identified the benefits of involving physicians in leadership roles in the health care system ( Crocitto et al , 2021 ; Denis et al , 2013 ; Grimes et al , 2012 ; Jolemore and Soroka, 2017 ; Stoller, 2009 ) there is relatively little information available on family physicians’ leadership roles during a public health crisis. Existing studies of family physician leadership focus on leadership in interdisciplinary teams ( Brown et al , 2015 ; Brown et al , 2021 ; Brown and Ryan, 2018 ; Szafran et al , 2018 ), the need for more leadership training ( Gallagher et al , 2017 ; Kelly et al , 2019 ) or physicians in academic leadership roles ( Krueger et al , 2017 ; Oandasan et al , 2013 ; White et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Academic physicians are not required to obtain formal leadership training before assuming a leadership role. This is true for team (8)(9)(10)(11)(12). It is beyond the scope of this perspective to discuss the details of each program.…”
Section: Physician Leadership Trainingmentioning
confidence: 85%